The Dynamics of Lamin a During the Cell Cycle - Vivante, Anat; Shoval, Irit; Garini, Yuval (Frontiers in Molecular Biosciences, 2021)
Lamin proteins play an essential role in maintaining the nuclear organization and integrity; and lamin A, in particular, plays a major role in the whole volume of the nuclear interior. Although the nucleus is highly organized, it is rather dynamic, it affects crucial nuclear processes and its organization must change as cells progress through the cell cycle. Although many aspects of these changes are already known, the role of lamin A during nuclear assembly and disassembly as well as its underlying mechanisms remains controversial. Here we used live cells imaging and Continuous Photobleaching (CP) method to shed light on the dynamics and mechanisms of lamin A during the cell cycle, combined with imaging flow cytometry measurements, which provides the high-throughput capabilities of flow cytometry with single-cell imaging. As a major analysis tool, we used spatial correlation algorithm for allocating the distribution of lamin A, chromatin and tubulin, as well as their mutual colocalization. Furthermore, we analyzed the distribution of lamin A along the nuclear lamina and in the nucleus interior during the cell cycle. Our results indicate that at the beginning of the cell division that include prophase, metaphase and anaphase, lamin A is distributed throughout the cytoplasm and its concentration in the chromosomal regions is reduced, whereas the spatial correlation between lamin A and tubulin is increased. It implies that lamin A also disassembled in the whole cellular volume. At the telophase and early G1, lamin A is concentrated in the whole volume of the newly formed nuclei of the daughter cells and it assembles to the lamina. We also explored the functional aspects of lamin A during the cell cycle and its binding to the chromatin versus the freely diffusion form. We found that the fraction of the bound proteins of lamin A in the S phase increased, relative to the G1 phase, which means that during replication, the concentration of lamin A on the chromatin increases. All these results shed light on the function of lamin A throughout the cell cycle.